ANALYSIS OF MARKET LOSSES AND MARKET OPPORTUNITIES OF UKRAINIAN ENTERPRISES DURING THE WAR - KRASOVSKYI, Oleksandr; STADNYK, Valentyna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Active economic activity of enterprises is one of the key factors of Ukraine’s stability during the war. Its importance goes beyond purely economic indicators: enterprises support domestic demand, provide employment, generate tax revenues, and maintain the basic living conditions of the population. Experience shows that even in periods of crisis, some entities suffer losses, while others find new opportunities for development, using changing market and social conditions to their advantage. The aim of the article is to structure the volume of economic losses suffered by Ukrainian business since the beginning of the war by type of economic activity and correlate them with new market opportunities that can be realized during the war and after it. Based on the structural and dynamic analysis of the state of the Ukrainian economy in the period 2020-2024, those spheres of economic activity that suffered the greatest losses during the war and those that were able to recover the fastest were highlighted. The importance of preserving the export capabilities of the Ukrainian economy was emphasized. The deterioration of the dynamics of export revenue was noted, especially in industries that formed the basis of Ukraine’s export capacity. The ambiguity of the development of the IT sector, which is one of the promising in the era of digitalization, shows good dynamics of the implementation of export opportunities, but faced institutional risks that increased the risk of personnel loss. The key risk factors that are most evident in various sectors of the economy during the war are identified and systematized, and ways to minimize those that are subject to local control (organizational, personnel, logistical, information and reputational risks) are outlined. Ways of creating new market opportunities in terms of types of economic activity and the conditions for their implementation are outlined. It is emphasized that business should be proactive, flexible and strategically oriented, able to form functional strategies adequate to market challenges and ensure their effective implementation, using modern tools and technologies.